Pengembangan E- Modul Berbasis Problem Based Learning pada Mata Pelajaran Ekonomi Kelas X untuk Meningkatkan Prestasi Belajar Siswa Tahun 2020 - saifudin yusuf (Jurnal Pendidikan : Riset dan Konseptual, 2020)
Abstract : This study aims to: 1). To determine the validity of the economic teaching instrument using e-modules based PBL to learning achievement can guarantee the research results. 2). To determine the effectiveness of development e-modules based PBL to improve students' ability learning achievement in SMA Islam Sunan Gunung Jati. This research and development used research & development module, according to Borg & Gall, 1983. The populations of this study were 252 students. Development of samples was done by using simple random sampling: the sample totaled 152 students. The analysis data used Descriptive and T-test of two independent samples that have previously been tested in the form prerequisite normality test, homogeneity and the average balance. Based on the results of the validity of the economic teaching instrument using e-modules based PBL to learning achievement validation study concluded that as many media experts 96, 25% with very good criteria, material experts and strategy as much as 95,55% with very good criteria, expert practitioners of RPP as much as 94,69% with very good criteria, syllabus as many as 92, 00% with the criteria very well. Based on the results of the effectiveness testing analysis concluded that: 1). at the trial produces t-test Value t-hitung > t-tabel (10,936 > 1,9977). 2) The limited testing t-test Value t-hitung > t-tabel (20,936 > 1,9944). 3) The use of trials tested using t-test two independent samples using separated variance with the results for t-hitung (3,289) > t-table (2,101) due to t-hitung> t-table. The conclusionis the use of e-modules based on problem based learning is better than LKS based on problem-based learning in terms of improving students' learning achievement. Based on the results of learning achievement students gain normalized scores were analyzed with the yield on the experimental class learning achievement abilities high category as high is 87,5%, medium is 12,5% low is much as 0%. While the to learning achievement in the control class of students whose high category as high is 50,5% of students, while medium is 57,5% of students, low is 0%.